Purple glove syndrome - Adrianna Szeliga; Dominika Spyt; Mateusz Kasinowicz (Kazimierz Wielki University, 2019)
Introduction: Purple glove syndrome is an atypical and adverse reaction to intravenous phenytoin, which is characterized by oedema, pain and a dark purple-bluish discolouration, typically located on an upper extremity. The clinical manifestation of this syndrome occurs in three stages: appearance, progression and resolution of symptoms. PGS develops up to 12 hours after administration of intravenous phenytoin and it disappears in a few weeks or months. Objective: The aim of this article is to summarize the current state of knowledge about purple glove syndrome: the pathophysiology, risk factors, the diagnosis and the current treatment. Brief descriptions of the state of knowledge: Despite many years PGS is still unexplained phenomenon. It is claimed that vascular tearing, micro-extravasation, alkaline pH of the solution or unidentified procoagulant mechanism can cause tissue impairment. The treatment depends on a limb elevation, physiotherapy, intravenous heparin administration, pain control, nitroglycerine application and a nerve blocks. To prevent PGS it is recommended to use oral phenytoin whenever possible, slow infusion rate of phenytoin less than 25mg/min, large cannula (20G or larger) in a large calibre vein and suitable, small doses. What is important fosphenytoin, a pro-drug of phenytoin, can also cause PGS, even though it was thought to be a safe drug, and a purple glove syndrome induced by fosphenytoin has never been described before. Summary: Despite the existence of many clinical trials, long term observations and scientific speculations, PGS can still be challenging for clinicians. There is a need for further scientific research to explain this phenomenon and to increase the awareness of this problem in general medical practice.